A case of premature ventricular contractions, ventricular tachycardia, and arrhythmic storm induced by right ventricular pacing during cardiac resynchronization therapy: Electrophysiological mechanism and catheter ablation. Issue 6 (15th July 2015) - Pedretti, Stefano; Vargiu, Sara; Paolucci, Marco; Lunati, Maurizio
Abstract: A 77‐year‐old man with ischemic cardiomyopathy and a cardiac resynchronization therapy‐defibrillator (CRT‐D) device came to our attention due to incessant ventricular tachycardia and multiple implantable cardioverter defibrillator (ICD) shocks. An electrocardiogram showed non‐sustained monomorphic ventricular tachycardias (NSVTs) constantly occurring after each biventricular stimulation. During an electrophysiological study, NSVTs reproducibly recurred only after right ventricular (RV) pacing; LV pacing did not induce any NSVTs. The activation map was consistent with a localized reentry at the interventricular septum, and a double exit; at the LV exit site, a single radiofrequency energy application immediately interrupted the occurrence of the NSVTs. Current evidence supports LV pacing to be pro‐arrhythmogenic in few CRT patients. This unusual case shows that RV pacing during CRT could produce frequent ventricular arrhythmias and arrhythmic storm. Catheter ablation can be considered an effective therapeutic option, especially when CRT maintenance is highly advisable.